Top Answer

x2 + 14x + 45 = 0 => x2 + 9x + 5x + 45 = 0 => x(x + 9) + 5(x + 9) = 0

(x + 9)(x + 5) = 0 so that x = -5 or x = -9

🙏

0🤨

0😮

0😂

0Loading...

x2 - 14x + 45 = (x - 9)(x - 5)

x2 - 14x + 45 = (x - 5)(x - 9).

-x2+14x=49

The roots are: x = -5 and x = -9

x2-14x+45=0(x-9)(x-5)=0x-9=0 & x-5=0x=9 & x=5

-x2-14x-45 = -(x2+14x+45) delta = 142-4*1*45=16 so x2+14x+45=(x-(-14+4)/2) (x-(-14-4)/2) = (x+5)(x+9) so -x2-14x-45 = -(x+5)(x+9)

(x2 + 14x + 49) = (x + 7)2

49 x2 + 14x = -7 x2 + 14x + 49 = 42 (x + 7)2 = 42 x = -7 ± √42

The given expression does not have rational factors, so the question cannot be abut factorising. Evaluating x2 - 14x + 9 depends on the value of x.

16x = -5 x = -.3125

x2 + 14x + 48 = (x + 8)(x + 6)

x2+14x+40 = (x+4)(x+10) when factored

x2 - 14x = -49 ∴ x2 - 14x + 49 = 0 ∴ (x - 7)2 = 0 ∴ x = 7

x2+14x+49 = (x+7)(x+7) when factored

49-apex

x2 - 14x + 49(x - 7) (x - 7)

x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7

51.07142857142857

doesnt make sense

x2 + 14x + 45 = (x + 9) (x + 5)

x2 - 14x + 49 = (x - 7)2

Do tou mean x2+14x+24? If so then it is (x+2)(x+12) when factored

x^2 + 14x + 40 factorises as (x + 10)(x + 4) so the roots are x = -10, -4.

35

Re-arranging, x2 - 14x +49 = 0 Factorising, (x-2)(x-2) = 0, hence x=2.